Montmorillonite-activated nanocarbon from pine wood sawdust and its biocomposites - Md Rezaur, Rahman; Durul, Huda; Al-Khalid, Hj Othman; Md. Shahid Uz, Zaman; Jamal, Uddin; Khairul Anwar, Mohamad Said; Yuriy, Yurkin; Andrey, Burkov; Muhammad Khusairy, Bakri; Kuok, Kuok King (Elsevier Ltd., 2024)
Due to plastic’s promising qualities, including corrosion resistance, low density, and user-friendly design, their manufacturing, and use have significantly risen over the last 60 years. The growth of the plastics industry has resulted in the development of various plastic products with broad applications using various plastics, such as the introduction of natural polymers, modified natural polymers, synthetic plastics, biodegradable plastics, thermoplastics, and thermosetting plastics. Fig. 8.1 depicts the global plastic demand broken down by polymer type (What Is Hot - Multi-client study, 2023). According to the information provided by Pardos Marketing (What Is Hot - Multi-client study, 2023), polypropylene (PP), accounts for 31% of high-demand plastic, low-density polyethylene (LDPE), and linear lowdensity polyethylene (LLDPE), accounts for 18% of high-demand plastic, and polyvinyl chloride (PVC), accounts for 14% of high-demand plastic (PVC).